Analisis Pengaruh Environmental, Social, and Governance (ESG) Score dengan Kinerja Keuangan pada Perusahaan Sektor Energi - Ghea Rahmayanti; Merry Susanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the effect of ESG scores on the financial performance of energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The research employs a quantitative approach using panel data regression analysis. The sample consists of 11 companies, resulting in a total of 33 observations, selected through a purposive sampling method. Financial performance is measured using Return on Assets (ROA), Return on Equity (ROE), and Tobin’s Q. Data processing was conducted using EViews version 12. The analyses included classical assumption tests consisting of normality, heteroscedasticity, and autocorrelation tests; panel data model selection tests consisting of the Chow Test, Hausman Test, and Lagrange Multiplier Test; as well as hypothesis testing consisting of the F-test, t-test, and coefficient of determination test. The results of the analysis do not support the hypothesis that ESG scores affect financial performance as measured by ROA, ROE, and Tobin’s Q.